Toxicokinetic Model Development for the Insensitive Munitions Component 3-Nitro-1, 2, 4-Triazol-5-One. (September 2015) - Sweeney, Lisa M.; Phillips, Elizabeth A.; Goodwin, Michelle R.; Bannon, Desmond I.
3-Nitro-1, 2, 4-triazol-5-one (NTO) is a component of insensitive munitions that are potential replacements for conventional explosives. Toxicokinetic data can aid in the interpretation of toxicity studies and interspecies extrapolation, but only limited data on the toxicokinetics and metabolism of NTO are available. To supplement these limited data, further in vivo studies of NTO in rats were conducted and blood concentrations were measured, tissue distribution of NTO was estimated using an in silico method, and physiologically based pharmacokinetic models of the disposition of NTO in rats and macaques were developed and extrapolated to humans. The model predictions can be used to extrapolate from designated points of departure identified from rat toxicology studies to provide a scientific basis for estimates of acceptable human exposure levels for NTO.